Gene ompR and regulation of microcin 17 and colicin e2 syntheses. - Hernández-Chico, C (1982)
The production of microcin 17 is controlled by plasmid pRYC17. Chromosomal mutants unable to produce a normal amount of microcin were isolated in Escherichia coli. One of the mutations maps in the ompR locus, indicating that an active OmpR product is required for the synthesis of microcin 17. The same conclusion was obtained for the synthesis of colicin E2. Therefore, two new functions of the regulatory gene ompR have been revealed.